ECEL1 mutation causes fetal arthrogryposis multiplex congenita. (23rd February 2015) - Dohrn, N.; Le, V.Q.; Petersen, A.; Skovbo, P.; Pedersen, I.S.; Ernst, A.; Krarup, H.; Petersen, M.B.
Abstract : Arthrogryposis multiplex congenita (AMC) is a descriptor for the clinical finding of congenital fixation of multiple joints. We present a consanguineous healthy couple with two pregnancies described with AMC due to characteristic findings on ultrasonography of fixated knee extension and reduced fetal movement at the gestational age of 13 weeks + 2 days and 12 weeks + 4 days. Both pregnancies were terminated and postmortem examinations were performed. The postmortem examinations confirmed AMC and suggested a diagnosis of centronuclear myopathy (CNM) due to characteristic histological findings in muscle biopsies. Whole exome sequencing (WES) was performed on all four individuals and the outcome was filtered by application of multiple filtration parameters satisfying a recessive inheritance pattern. Only one gene, ECEL1, was predicted damaging and had previously been associated with neuromuscular disease or AMC. The variant found ECEL1 is a missense mutation in a highly conserved residue and was predicted pathogenic by prediction software. The finding expands the molecular basis of congenital contractures and the phenotypic spectrum of ECEL1 mutations. The histological pattern suggestive of CNM in the fetuses can expand the spectrum of genes causing CNM, as we propose that mutations in ECEL1 can cause CNM or a condition similar to this. Further investigation of this is needed and we advocate that future patients with similar clinical presentation or proven ECEL1 mutations are examined with muscle biopsy. Secondly, this study illustrates the great potential of the clinical application of WES in couples with recurrent abortions or stillborn neonates. © 2015 Wiley Periodicals, Inc.